Pregnancy in Sickle Cell Disease Is a Very High-Risk Situation: An Observational Study - Narcisse Elenga; Aurélie Adeline; John Balcaen; Tania Vaz; Mélanie Calvez; Anne Terraz; Laetitia Accrombessi; Gabriel Carles (Obstetrics and Gynecology International)
Sickle cell disease is a serious genetic disorder affecting 1/235 births in French Guiana. This study aimed to describe the follow-up of pregnancies among sickle cell disease patients in Cayenne Hospital, in order to highlight the most reported complications. 62 records of pregnancies were analyzed among 44 females with sickle cell disease, between 2007 and 2013. Our results were compared to those of studies conducted in Brazil and Guadeloupe. There were 61 monofetal pregnancies and 2 twin pregnancies, 27 pregnancies among women with SS phenotype, 30 SC pregnancies, and five S-beta pregnancies. The study showed that the follow-up of patients was variable, but no maternal death was found. We also noted that the main maternofetal complications of pregnancies were anemia (36.5%), infection (31.7%), vasoocclusive crisis (20.6%), preeclampsia (17.5%), premature birth (11.1%), intrauterine growth retardation (15.9%), abnormal fetal heart rate (14.3%), and intrauterine fetal death (4.8%). Pregnancies were more at risk among women with SS phenotype. Pregnancy in sickle cell disease patients requires a supported multidisciplinary team including the primary care physician, the obstetrician, and the Integrated Center for Sickle Cell Disease.